Method and technique of 3-D dynamic structural evolution modelling of fault basin. (1st January 2013) - Zhang, Zhiting; Wu, Chonglong; Mao, Xiaoping; Yao, Wei
The important and difficult point in the 3-D basin structural evolution modelling is how to make the modelling conform to the real geological process. In this paper, the rectification of formation boundary deformation is implemented by 3-D flexural slip mechanism and shearing mechanism. In compaction correction, by taking account of the phase boundary and diagenetic effect on porosity, a formwork of the porosity-depth change characteristic is obtained by 'plane divisional and longitudinal zoning' method, and then the porosity data of grid cells in different geological times are calculated using compaction correction algorithm, and finally the decompaction correction calculation is finished based on volume-balance technique. Using this modelling method to simulate the structural evolution of Niuzhuang-Wangjiagang region in Dongying Sag, the 3-D dynamic evolution models of geologic body from the upper section of the 4th member of Shahejie formation to present are figured out and they are according with the process of the historical and spatial modality of geological structure development. It demonstrates that this method has certain practicality and can express the process of geological structure development effectively.